A High-Efficiency Broadband Superconducting Nanowire Single-Photon Detector with a Composite Optical Structure**Supported by the National Basic Research Program of China under Grant Nos 2011CBA00100 and 2011CBA00200, the National Natural Science Foundation of China under Grant Nos 11227904 and 61101012, the National High-Technology Research-Development Program of China under Grant No 2011AA010204, and the Jiangsu Key Laboratory of Advanced Techniques for Manipulating Electromagnetic Waves. (March 2015) - Gu, Min; Kang, Lin; Zhang, La-Bao; Zhao, Qing-Yuan; Jia, Tao; Wan, Chao; Xu, Rui-Ying; Yang, Xiao-Zhong; Wu, Pei-Heng
<x content-type="archive" xml:space="preserve">Abstract</x> Superconducting nanowire single-photon detectors (SNSPDs) with a composite optical structure composed of phase-grating and optical cavity structures are designed to enhance both the system detection efficiency and the response bandwidth. Numerical simulation by the finite-difference time-domain method shows that the photon absorption capacity of SNSPDs with a composite optical structure can be enhanced significantly by adjusting the parameters of the phase-grating and optical cavity structures at multiple frequency bands. The absorption capacity of the superconducting nanowires reaches 70%, 72%, 60.73%, 61.7%, 41.2%, and 46.5% at wavelengths of 684, 850, 732, 924, 1256, and 1426 nm, respectively. The use of a composite optical structure reduces the total filling factor of superconducting nanowires to only 0.25, decreases the kinetic inductance of SNSPDs, and improves the count rates.